RESERVOIR CHARACTERIZATION AND VOLUMETRIC ESTIMATION OF UPPER MIOCENE TURBIDITIC SANDSTONE, MR70X INTERVAL, MAZMUR FIELD, KUTAI BASIN, EAST KALIMANTAN - Christian Hetharia, Joshua
Mazmur Field is one of the operating field in Kutai Basin, East Kalimantan under operated by PT. CPI, which covers 120 kilometres2 area and already entered the development stage by 2016 since the exploration stage on 1999. The purpose of this study research is to determine the facies, characterize the reservoirs based on distribution and petrophysical properties, and estimate the volumetric of the reservoir, which use log data from seven wells, biostratigraphy data, core data from the analog well (JW4), and 3D seismic data. Mazmur Field has a regional marker within Upper Miocene age with the object/interval of this research is MR70X. The research conducted by the student on this study object concludes that this field consists of three reservoirs (reservoir 1, reservoir 2, and reservoir 3) with eight lithofacies and facies associations Sub-marine Channel, Channel Margin, Levee Overbank, Hemipelagic, within deepmarine depositional environment. Reservoir distribution analyzed with minimum amplitude data with the distribution along West-East. The results from petrophysical analysis under those three reservoirs which shown in the reservoir summary conclude this, reservoir 1 have an average volume of shale 0,372, average effective porosity 0,246, average effective water saturation 0,605, and reservoir 2 have an average volume of shale 0,511, average effective porosity 0,134, average effective water saturation 0,623, also reservoir 3 have an average volume of shale 0,620, average effective porosity 0,138, and average effective water saturation 0,744. Volumetric estimation details on Mazmur Field is 24717 million STB on reservoir 1, 12909 million STB on reservoir 2, and 386 million STB on reservoir 3 with th